Use of social networking applications by immigrant children, adolescents, and young adults to maintain contact with those who remained in the country of origin: usage characteristics and habits. (30th March 2020) - Zilka, Gila Cohen
In the present research, we examined the use and its influence of social networking applications on the process of young immigrants' acclimatisation in Israel, given the widespread use of such applications by children, adolescents, and young people to maintain contact with those who remained in their country of origin. This is a mixed-method study. A total of 551 participants from Israel completed questionnaires, of whom 110 were also interviewed. Interviewees were asked to clarify the quantitative findings to help gain in-depth understanding of the factors affecting acclimatisation. The semi-structured interviews covered all the topics included in the research questionnaires. The interviewees wanted to share positive and negative experiences they lived through, and some provided detailed descriptions. The study found that participants feel that communication alleviates the sense of longing, enables intimate discourse, sentiment sharing, release of anger, and relief of frustration. The use of web applications encourages significant interactions with those who remained in the country of origin, but to a certain extent causes social isolation in the new country.